2010
DOI: 10.1111/j.1533-2500.2009.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Utility Analysis of Interdisciplinary Early Intervention Versus Treatment as Usual For High-Risk Acute Low Back Pain Patients

Abstract: Chronic pain is a costly and debilitating condition that has proven difficult to treat, solely with medical interventions, due to the complex interplay of biological, psychological, and social factors in its onset and persistence. Many studies have demonstrated the effectiveness of interdisciplinary treatment that includes psychosocial interventions for low back pain. Nevertheless, these interventions continue to be under-utilized due to concerns of cost and applicability. The present study utilized a cost uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Sequence generation has been achieved through a "congruential multiplier" statistical algorithm application, using IBM Statistical Package for Social Sciences (SPSS) Version 19 [21,22] and was stratified with 1:1 allocation random block size of 36. The randomization list reports a progressive randomization number for randomized participants (from 1 to 72), and the treatment (A or B) will be assigned for each of them.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence generation has been achieved through a "congruential multiplier" statistical algorithm application, using IBM Statistical Package for Social Sciences (SPSS) Version 19 [21,22] and was stratified with 1:1 allocation random block size of 36. The randomization list reports a progressive randomization number for randomized participants (from 1 to 72), and the treatment (A or B) will be assigned for each of them.…”
Section: Methodsmentioning
confidence: 99%
“…7 Cost analyses of health care interventions are essential in today's ever-changing health care field to ensure quality care while health care costs continue to increase annually. 8,9 Therefore, the authors of this article propose that home delivery of chemotherapy is an example of a PC intervention that can improve the QOL of pediatric oncology patients, foster a cost savings plan, and also support the WHO definition of PC.…”
mentioning
confidence: 97%
“…Also, in several studies, investigators have reported that a major benefit of outpatient delivery of chemotherapy results in significant reduced health care costs (ie, due to decreased hospital admissions). 8,9,[11][12][13] Standard risk medulloblastoma (SRMB) patients spend approximately 14 months after diagnosis undergoing radiation and chemotherapy. Because survival has improved to almost 90%, 14 it is imperative to focus not only on the QOL of survivors but also on the patient's QOL while receiving oncology treatments.…”
mentioning
confidence: 99%
“…This interdisciplinary approach is aimed at tailoring treatment to individual-patient needs in order to promote maximum rehabilitation in both physical and psychosocial areas, using a combination of cognitive behavioral therapy (CBT), physical conditioning, and psychosocial evaluations that are carefully monitored by a team of health-care professionals [18][19][20]. This approach has been shown to be highly effective, both therapeutically and in terms of cost effectiveness [21][22][23]. Other forms of physical modalities for pain management that have been studied and displayed to have some promising results in aiding pain relief include myofascial-release therapy, chiropractic care, and exercise to improve coordination/stabilization, strength/resistance, and cardiovascular training groups [24][25][26].…”
mentioning
confidence: 99%